2011
DOI: 10.1111/j.1600-0579.2010.00629.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental students’ knowledge of ergonomic postural requirements and their application during clinical care

Abstract: The knowledge of ergonomics postural requirements and their clinical application among the dental students surveyed were not satisfactory. The reasons for the learning difficulties encountered by the students should be identified to improve the learning process. The didactic use of digital images in this study may help in this endeavour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
72
1
14

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(99 citation statements)
references
References 6 publications
12
72
1
14
Order By: Relevance
“…This study has observed many incorrect postures, both of spine (47.76%) and neck (73.13%) projecting them a lot to the front, laterally or performing rotations; and legs (91.04%) being unable to maintain the angle between thigh and leg in an interval of 90 and 120 degrees; and association with musculoskeletal pain during and after procedures. Garbin et al 12 have observed that the reason for a poor posture may be associated to lack of knowledge about the right posture. Other studies associate working hours and excessive number of patients per period as influencing occupational pain 6,21,22,29 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study has observed many incorrect postures, both of spine (47.76%) and neck (73.13%) projecting them a lot to the front, laterally or performing rotations; and legs (91.04%) being unable to maintain the angle between thigh and leg in an interval of 90 and 120 degrees; and association with musculoskeletal pain during and after procedures. Garbin et al 12 have observed that the reason for a poor posture may be associated to lack of knowledge about the right posture. Other studies associate working hours and excessive number of patients per period as influencing occupational pain 6,21,22,29 .…”
Section: Discussionmentioning
confidence: 99%
“…These complaints are primarily related to neck, shoulders and cervical and lumbar spine pain, similar to those found in most studies 1,21,22,26,28 , stressing that poor posture-related health problems are still afflicting professionals, in spite of technological advances. To consider professionals correctly positioned on the bench, they should sit symmetrically erect and most possible to the back, allowing the sternum bone to be slightly advanced and raised, abdominal muscles should be smoothly compressed and back should be supported by posterior hip bones 12,18 . Primary dentists' difficulty is the accurate visualization of the surgical field, forgetting the right posture, excessively bending the neck, very often followed by its rotation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known, that it is not so easy to apply ergonomic knowledge in clinical practice for dentists who are not used to work in ergonomic way. Ergonomics is a discipline which requires a profound and systematic approach, regular practical training and control [21][22][23]. Therefore the promotion of ergonomics in dentistry should be highly encouraged by universities, Lithuanian Association of Dental Ergonomics and all the organizers of postgraduate courses in Lithuania.…”
Section: Discussionmentioning
confidence: 99%